(untitled) (lectio difficilior, 2019)
This article is a translation of Marianne Grohmann’s article “Metaphors of Miscarriage in the Psalms” (2019).[1] It applies the conceptual blending theory of metaphor to a specific imagery in the Psalms: metaphors of miscarriage and stillbirth. It asks whether miscarriage is considered a real threat or a “mere” metaphor in these texts, and situates the texts within the conceptual systems about miscarriage and stillbirth in the Hebrew Bible and the Ancient Near East. In the Psalms, miscarriage and stillbirth are described by three terms with different connotations: שׁכל (bereavement) in Psalm 35:12, נפל (falling down) in Psalm 58:9, and יצא (going forth/coming out) in Psalm 144:14. Conceptual blending offers a framework to integrate both “literal” and “metaphoric” references to miscarriage in the Psalms.